Parliament, treaties and international law - Shuaib, Farid Sufian; Mohd Kamal, Mohd Hisham (Sweet & Maxwell, 2020)
This chapter discusses the role of Parliament in negotiating the terms and in deciding to become a party to international treaties. In discussing the role of Parliament, the deliberation touches on the role of the Executive in ratifying concluding treaties and of the judiciary in applying treaties, to ensure a comprehensive treatment of the subject. Reference is made to relevant provisions in the Federal Constitution of Malaysia as the supreme law of the land. The Federal Constitution provides the distribution of powers between the three organs of government the State, namely: the Executive, the Legislature and the Judiciary.